2015
DOI: 10.2147/rrb.s58514
|View full text |Cite
|
Sign up to set email alerts
|

Examining the evidence for major histocompatibility complex-dependent mate selection in humans and nonhuman primates

Abstract: Compounds of the major histocompatibility complex (MHC) are integral for effective vertebrate adaptive immune response, and are also implicated as cues for sexual selection. The evidence for this is supportive of MHC-based preference for diverse and dissimilar mating partners, in a range of vertebrates from fish to nonhuman primates. However, the evidence for a similar role of these genes and the evolutionary benefits of their diversity in human mate choice has been more controversial. Here, we review the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 161 publications
(178 reference statements)
1
30
0
Order By: Relevance
“…Another methodological source of heterogeneity we tested was choice cue because preferences based on different stimuli could show different patterns, but we found no strong evidence of this and other studies have found positive correlation between facial and scent attractiveness (Thornhill & Gangestad 1999;Thornhill et al 2003). Additional methodological differences between human studies and their implications for results have been thoroughly discussed elsewhere (Wedekind et al 2002;Havlicek & Roberts 2009;Derti et al 2010;Winternitz & Abbate 2015). We note that we cannot unanimously differentiate whether the differences between study outcomes are caused by methodology or biology, and it is likely that both types of mechanisms are in effect.…”
Section: Methodological Differences Among Studiesmentioning
confidence: 72%
See 4 more Smart Citations
“…Another methodological source of heterogeneity we tested was choice cue because preferences based on different stimuli could show different patterns, but we found no strong evidence of this and other studies have found positive correlation between facial and scent attractiveness (Thornhill & Gangestad 1999;Thornhill et al 2003). Additional methodological differences between human studies and their implications for results have been thoroughly discussed elsewhere (Wedekind et al 2002;Havlicek & Roberts 2009;Derti et al 2010;Winternitz & Abbate 2015). We note that we cannot unanimously differentiate whether the differences between study outcomes are caused by methodology or biology, and it is likely that both types of mechanisms are in effect.…”
Section: Methodological Differences Among Studiesmentioning
confidence: 72%
“…; Havlicek & Roberts ; Derti et al . ; Winternitz & Abbate ). We note that we cannot unanimously differentiate whether the differences between study outcomes are caused by methodology or biology, and it is likely that both types of mechanisms are in effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations